2013
DOI: 10.1177/0165551513477820
|View full text |Cite
|
Sign up to set email alerts
|

Understanding trust formation in digital information sources: The case of Wikipedia

Abstract: This article contributes to knowledge on how users establish the trustworthiness of digital information. An exploratory two-stage study was conducted with Master’s and undergraduate students in information studies. In the first phase of the study respondents commented on the factors and processes associated with trust formation. Participants commented on authorship and references, quality of writing and editing, and verification via links to external reference sources. Findings from the second phase, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…As much as human relationships are largely dependent on mutual trust, the quality, depth, and length of the use of a technology or service is also significantly affected by users' trust in it. For example, greater trust in a website (Rowley, & Johnson, 2013) or advertisement (Soh, Reid, & King, 2009) is known to increase usage of and purchase intention for the website and advertised product, respectively. In the business sector, trust is found to be a primary determinant of sales effectiveness and consumer-service provider relationships (Johnson, & Grayson, 2005).…”
Section: Perceptions and Evaluations Of Autonomous Vehiclesmentioning
confidence: 99%
“…As much as human relationships are largely dependent on mutual trust, the quality, depth, and length of the use of a technology or service is also significantly affected by users' trust in it. For example, greater trust in a website (Rowley, & Johnson, 2013) or advertisement (Soh, Reid, & King, 2009) is known to increase usage of and purchase intention for the website and advertised product, respectively. In the business sector, trust is found to be a primary determinant of sales effectiveness and consumer-service provider relationships (Johnson, & Grayson, 2005).…”
Section: Perceptions and Evaluations Of Autonomous Vehiclesmentioning
confidence: 99%
“…Similarly, in Sillence et al's [15] diary study of how patients evaluate and make use of online health information, design factors, such as clear layout, good navigation aids and interactive features, were found to contribute to the selection and trust of web sites. Rowley and Johnson [10], found that students expressed considerable interest in the structure, style and quality of writing of Wikipedia articles, and grammatical or other editorial or proofreading oversights, and these impacted on their trust judgements.…”
Section: Key Propositionsmentioning
confidence: 99%
“…PROMPT outlines six evaluation criteria, each criterion demanding questions to be answered concerning the evaluation of the information being considered [16]: A study was conducted to ascertain how users establish the trustworthiness of digital information [20]. In the first instance users commented on the factors and processes associated with trust formation, e.g.…”
Section: Evaluating Informationmentioning
confidence: 99%